Improvement mechanism of the oxidation resistance of Al-doped Ti(C, N)-based cermets: Influence of enriched Al in the subsurface oxide layer. (December 2022) - Li, A.Q.; Lin, N.; Xu, L.W.; Zhang, W.J.; Zhang, X.C.; Wang, Z.Y.; Ma, C.
Abstract: The effects of Al doping on the oxidation kinetics and oxidation mechanism of Ti(C, N)-based cermets were investigated systematically. During the preparation process, Al derived from decomposed AlN powders promoted the precipitation of (Ni, Co)3 Al nanoparticles in the binder phase of the cermets. The formation of (Ni, Co)(W, Mo)O4 and Co2 NiO4 oxides provided essential oxidation resistance for the cermets. The presence of (Ni, Co)3 Al nanoparticles was found to promote oxidation resistance by forming a continuous (Ni, Co)(Ti, Al)O3 layer within subsurface oxide layers. After 20 h of oxidation at 800 ℃, the weight gain of cermets containing 2.0 wt% AlN was only 67.49 % of that of the pure cermets. Highlights: Al-doped Ti(C, N)-based cermets were synthesized through powder metallurgical method. Al element promoted the dispersed precipitation of (Ni, Co)3 Al nanoparticles in the binder phase. The isothermal oxidation caused the formation of a continuous (Ni, Co)(Ti, Al)O3 matter in the subsurface oxide layer. The Al doping can enhanced the oxidation resistance of cermets obviously.